Gambaran Hemodinamik Pasien Sectio Caesarea Obesitas dengan Anestesi Spinal - Ahmad Zainullah; Anis Prabowo; Weni Hastuti; Fangky Dimas Syafei (Jurnal Rumpun Ilmu Kesehatan, 2021)
Background: Obesity is a pathological condition due to excessive fat accumulation than is needed for body function. Pregnant women with overweight and obesity are at high risk and have been shown to be associated with increased complications in pregnancy. Cesarean section is a surgery to deliver a fetus by opening the abdominal wall and uterine wall. Generally, in cesarean section, spinal anesthesia is performed. Objective: to determine the hemodynamic picture of obese caesarean section patients with spinal anesthesia. Method: The method used is observational analytic with a cross-sectional approach and consecutive sampling technique. Data analysis uses parametric statistics. The data in this study are the results of differences in obese and non-obese patients. Data collection techniques in this study include documentation and observation. Results: The pre-anesthesia results obtained an average systolic blood pressure = 138.31 ± 17.528, an average diastolic blood pressure = 82.54 ± 10.643 and an average pulse of 100.69 ± 15.315, while the results after 5 minutes obtained an average systolic blood pressure of 105.31 ± 12.572, an average diastolic blood pressure of 61.15 ± 11.753 and an average pulse of 99.54 ± 18.963. Conclusion: Changes in blood pressure and pulse before spinal anesthesia with after spinal anesthesia in obese patients undergoing cesarean section showed a decrease in blood pressure and pulse in the 5th minute after injection.